Issues on Training and Re-training Teachers of the Georgian Language and Literature at the Modern Stage - Maghlakelidze, Natela (Actual Problems of Kartvelology, 2013)
Current educational reforms in our country changed not only the content, but also the form of teaching Georgian language and literature. This is the reason why the national educational plan and subject standards which training and re-training of teachers should be based on were created. The conception concerning the training and professional development of teachers was drawn up (resolution N29, February 9, 2006). According to the prepared document, the right of teaching was given to BAs and MAs of Education after oneyear probationary period at school and having passed teacher certification exams. BAs were able to teach only primary grades, MAs could teach on primary, basic and secondary levels. This opinion had to be rejected soon as the number of MA students are not sufficient. Therefore, BAs were also allowed to teach, though they had to undergo the probationary period or have one-year working experience in order to take the teacher certification exams. The amendments to this law were made in 2012, according to which, all BAs were allowed to undertake this profession without probationary period. It was prepared the conception of training and career growth, but, unfortunately, this conception is mainly focused on re-training, rather than training of teachers. It is noted that students should get education in accordance with the teacher’s professional and subject standards and should be equipped by skills relevant to the educational standards. It is noteworthy that it is only given a 60-credit module in the conceptionand not the whole direction for those interested in teaching. It should be noted that the state will finance the direction of education at universitiesfrom the following year, but the fact is that out universities are not prepared for this.